Vitamin D deficiency prevention policies in Iran: a retrospective policy analysis - Aghapour, Baharak; Kheirouri, Sorayya; Alizadeh, Mohammad; Khodayari-Zarnaq, Rahim (Frontiers in Nutrition, 2023)
The prevalence of vitamin D deficiency (VDD) in Iran has been reported higher than the global level. This study aimed to assess VDD prevention policies in Iran through a policy analysis of agenda setting using multiple streams framework (MSF).Methods: Using Kingdon's MSF model, this qualitative analytical study was conducted to perform a policy analysis on vitamin D-related policies in Iran. The policy documents were reviewed, and in-depth interviews were conducted with stakeholders (n=27) using framework analysis method.To categorize data and extract the related themes, the MAXQDA version 10 was used.Results: According to Kingdon's MSF theory, the problem stream included the high prevalence of VDD among Iranian infants (23.3%), adolescents (76%), and adults (59.1%). The policy stream was identified to focus on preventing programs of non-communicable diseases in the health system. Political stream indicated that national and international supports could provide a political climate for this issue.According to our results, a window of opportunity for policymaking on VDD prevention has been opened. However, there are some challenges related to the implementation of these policies as follows: the dominance of a treatment-based view rather than prevention-based one in the health system, economic problems, and restricted access to health services due to the outbreak of coronavirus disease 2019 (COVID-19). To strengthen and implement VDD prevention policies, the stakeholders need support from high-level policymakers.